Transcriptomes of human mesenchymal cells isolated from the right ventricle and epicardial fat differ strikingly both directly after isolation and long‐term culture. (9th January 2019) - Stępniewski, Jacek; Florczyk‐Soluch, Urszula; Szade, Krzysztof; Bukowska‐Strakova, Karolina; Czapla, Justyna; Matuszczak, Sybilla; Jarosz‐Biej, Magdalena; Langrzyk, Agnieszka; Tomczyk, Mateusz; Rumieńczyk, Izabela; Kulecka, Maria; Mikuła, Michał; et al.
Abstract: Aims: Mesenchymal stromal cells isolated from different tissues are claimed to demonstrate similar therapeutic potential and are often incorrectly named mesenchymal stem cells. However, through comparison of such cells is lacking. This study aimed to compare the transcriptome of mesenchymal cells of the same phenotype isolated from the heart muscle and epicardial fat of the same patient, before and after culture. Methods and results: Cells were isolated from biopsies of the right ventricle and epicardial fat collected from five patients (three men and two women, mean age 59.4 ± 2.6) who underwent heart transplantation due to ischaemic cardiomyopathy. In both tissues, immunophenotyping revealed three distinct populations: (i)CD31 − CD45 − CD90 + CD34 + CD146 −, (ii) CD31 − CD45 − CD90 + CD34 − CD146 +, and (iii) CD31 − CD45 − CD90 − CD34 − CD146 +, of which only the first one could be grown after sorting. Material for RNA‐seq was collected from these cells before culture (250 cells) and at passage 6 (5000 cells). Transcriptomic analysis revealed that cells of the same phenotype (CD31 − CD45 − CD90 + CD34 + CD146 − ) upon isolation preferentially clustered according to the tissue of origin, not to the patient from whom they were isolated. Genes up‐regulated in the right ventricle‐derived cells were related to muscle physiology while down‐regulated genes included those encoding proteins with transmembrane signalling receptor activity. After six passages, heart‐derived and fat‐derived cells did not acquire similar transcriptome. Cells isolated from the right ventricle in comparison with their epicardial fat‐derived counterparts demonstrated higher level of transcripts related, among others, to RNA processing and muscle development. The down‐regulated genes were involved in the nucleosome assembly, DNA packaging and replication, and interleukin‐7‐mediated signalling pathway. Cells from epicardial fat demonstrated higher heterogeneity both before and after culture. Cell culture significantly changed gene expression profile within both tissues. Conclusions: This study is an essential indication that mesenchymal cells isolated from different tissues do not demonstrate similar properties. Phenotypic identification and ease of isolation cannot be considered as a criterion in any therapeutic utilization of such cells.